2011
DOI: 10.1007/s12221-011-0864-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on ion conduction behaviour in Zn-ferrite based polymer nanocomposite electrolyte

Abstract: Present paper deals with, improvement in ion transport property and dielectric relaxation of polyethylene oxide (PEO)-based polymer electrolytes subsequent to dispersal of nanosized Zn-ferrite filler particles. The nanocomposite polymer electrolyte (NCPE) system [93PEO:7NH 4 SCN]: x% Zn-ferrite was prepared by solution cast technique through dispersal of sol gel derived Zn-ferrite nano powder in the pristine polymer electrolyte solution. The structural and morphological behavior of NCPEs have been studied by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The high value of ( ε ′ and ε ′′) in low frequency region might be due to existence of an electrode and interfacial polarization—The Maxwell–Wagner–Sillars effect. [ 26 ] It is clear that this effect is only observed at temperature higher than 343 K. In general, the electrode polarization is attributed to the blocking charge carriers at electrode, which is clarifying the abnormal increase of the real permittivity at low frequencies and high temperatures. On the other hand, an interfacial polarization means the polarization takes place at interface of existence of crystallinity, absorved water and presence of heterogeneity.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The high value of ( ε ′ and ε ′′) in low frequency region might be due to existence of an electrode and interfacial polarization—The Maxwell–Wagner–Sillars effect. [ 26 ] It is clear that this effect is only observed at temperature higher than 343 K. In general, the electrode polarization is attributed to the blocking charge carriers at electrode, which is clarifying the abnormal increase of the real permittivity at low frequencies and high temperatures. On the other hand, an interfacial polarization means the polarization takes place at interface of existence of crystallinity, absorved water and presence of heterogeneity.…”
Section: Resultsmentioning
confidence: 90%
“…This feature is typical of nanocomposite polymer electrolytes. [24][25][26][27][28] XRD studies have shown intercalation of TiO 2 in pristine electrolyte. This intercalation is likely to promote dissociation of salt leading to enhancement in the value of carrier concentration thereby causing increase in conductivity values Polymer-filler-salt interaction has also been noticed in XRD profiles (Figure 1).…”
Section: Resultsmentioning
confidence: 99%